Influence of phosphorylation on caspase-3-mediated Akt1 cleavage - Jahani-asl, Arezu (University of Ottawa (Canada), 2005)
Caspase-3, an executioner of apoptosis, is negatively regulated by X-linked inhibitor of apoptosis protein (XIAP), a determinant of cisplatin resistance. XIAP down-regulation in ovarian cancer cells or treatment with cisplatin induces caspase-3-mediated AKT cleavage and apoptosis, while XIAP over-expression suppresses this cleavage and increases phospho-AKT content. The identity of the caspase-3 cleavage site(s) in AM and the possible dependence of caspase-3-mediated cleavage on its phosphorylation status are unknown. The objectives of this thesis were to determine the caspase-3 cleavage site(s) in Akt1 and to examine the influence of phosphorylation on Akt1 cleavage in vitro. Our results suggested presence of three non-consensus (EEEE 117, EEMD119, DAKE398) and one consensus (DQDD456) cleavage sites, and posphorylation of Akt1 influenced the pattern of cleavage in a site-specific manner: Whereas cleavage at site "EEEE117" was facilitated by phosphorylation, that at sites "EEMD119 and DAKE398'' were attenuated. The biological significance of these observations requires future investigation.
Keywords: Biology, Molecular.; Biology, Cell.